2016
DOI: 10.1016/j.reprotox.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and maternal alcohol use: Prevalence and effects on child outcomes and fetal alcohol spectrum disorders

Abstract: Objective Determine any effects that maternal alcohol consumption during the breastfeeding period has on child outcomes. Methods Population-based samples of children with fetal alcohol spectrum disorders (FASD), normally-developing children, and their mothers were analyzed for differences in child outcomes. Results Ninety percent (90%) of mothers breastfed for an average of 19.9 months. Of mothers who drank postpartum and breastfed (MDPB), 47% breastfed for 12 months or more. In case control analyses, chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 49 publications
4
57
1
Order By: Relevance
“…These findings support and extend upon the findings of Gibson and Porter [7], who found dose-dependent reductions in children's abstract reasoning abilities at age 6-7 years. They are also consistent with the poorer grammatical comprehension observed in children of mothers who consumed alcohol while breastfeeding [39]. Furthermore, child [53] and maternal age [50], income [52], maternal education [52], birthweight [24], sex [51], tobacco smoking [1,4] and alcohol consumption during pregnancy [2,3] were all associated with academic scores in manners consistent with prior research.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These findings support and extend upon the findings of Gibson and Porter [7], who found dose-dependent reductions in children's abstract reasoning abilities at age 6-7 years. They are also consistent with the poorer grammatical comprehension observed in children of mothers who consumed alcohol while breastfeeding [39]. Furthermore, child [53] and maternal age [50], income [52], maternal education [52], birthweight [24], sex [51], tobacco smoking [1,4] and alcohol consumption during pregnancy [2,3] were all associated with academic scores in manners consistent with prior research.…”
Section: Discussionsupporting
confidence: 87%
“…No association was observed in babies who had never been breastfed. These findings were consistent with the poorer grammatical comprehension [39] and dose-dependent reduction in abstract reasoning ability observed in children of mother's who drank alcohol while breastfeeding [7]. This suggests that alcohol consumed during lactation can impact the academic achievement of children.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar questions have been used effectively and successfully in other ZA studies by our team and other experienced researchers (Jacobson et al, 2008; Viljoen et al, 2002). Proximal variables assessed included alcohol use by quantity, frequency, and timing during pregnancy and when breastfeeding (May et al, 2016c). Distal variables of maternal risk were addressed, including: maternal height, weight, and OFC; childbearing history; and demographic variables.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, we found notable differences in facial dysmorphology caused by prenatal alcohol exposure between the Cape Coloured and Caucasian cohorts related to midline and nonmidline structures. May and colleagues (, ) addressed the role of nutrition in FASD in the South African population (both in Reproductive Toxicology ). In the 2014 article, all of the mothers of both FASD and controls were found to be undernourished, but the mothers of children with FASD were more malnourished especially in calcium, docosapentaenoic acid, riboflavin, and choline, all nutrients important to growth and development and therefore could influence brain (head) and facial development.…”
Section: Discussionmentioning
confidence: 99%